Comparative analysis of the efficacy of topical negative pressure dressing with conventional wound dressing in wound healing - Koppad, Sanjay N.; Badiger, Suresh; Desai, Mallikarjun; Kodliwadmath, Harsha (International Surgery Journal, 2016)
Background:Wounds and their management are fundamental to the practice of surgery. In the past 15 years there have been significant advances in complex acute and chronic wound management. One of the one of the most significant discoveries was the improvement in wounds with negative pressure–assisted wound closure. In this study, the efficacy of topical negative pressure dressing with that of a control group using conventional moist wound dressings, in healing of wounds, was assessed with quality of wound healing. Methods: This is a prospective randomized observational study, 50 patients visiting medical college hospital with acute and traumatic wounds, sub-acute wounds, chronic open wounds, of which 25 patients underwent topical negative pressure dressing. The remaining 25 patients underwent conventional moist wound dressings. Wounds were assessed depending on wound size and percentage of reduction of wound size, wound bed score, percentage of granulation tissue cover, graft take up as the percentage of ulcer surface area. Statistical analysis was done using unpaired students T test and paired T test. A p-value <0.05 was taken as significant. Results:Our study shows statistically significant reduction in wound size, in the study group 19.52 square centimetres (cm2) as compare to control group i.e. 6.64 cm2 (p<0.001). There is significant increase in wound bed score in the study group (mean difference was 9.60±2.16) where as in the control group there was not much increase in wound bed score (mean difference was 5.12±1.99) (p valve 0.00001). The percentage of granulation tissue formation in the study group was 81.0±8.29 and in the control group was 53.60±19.23 (p value=0.00001). The percentage of graft take up in the study group was 83.42±4.43 and in the control group was 63.18±11.24 (p value=0.00001). The mean hospital stay and cost of hospital stay is also reduced in topical negative pressure dressing group when compared to conventional wound dressings group. Conclusions:It is concluded that topical negative pressure dressing is better the conventional wound dressings in wound healing.